Theoretical aspects of strategy of competitiveness of firm (Journal of Economic Research & Business Administration, 2016)
An ultimate goal of any commercial organization is receiving profit that can be reached only by a victory in competitive fight. Achievement of such victory depends on competitiveness of goods, works and services which are represented by firm in the market. In the last time the concept of competitiveness became more than fashionable. Competitive advantages of firm are provided in the course of competitive fight against the socalled five directions of the competition: with other sellers of similar produc tion; firms – potential competitors; producers of substitutes; suppliers of resources; buyers of its production. They are considered as the main mar ket forces. The defining elements of strategy are decisions on placement of resources, adaptation to environment, internal coordination, creation of long competitive advantages.
Keywords: strategy; competitiveness of firm; competitive advantages; competitiveness factors; cometition.